Systemic regulation of retinal medium-chain fatty acid oxidation repletes TCA cycle flux in oxygen-induced retinopathy - Almut Heinken; John M. Asara; Gopalan Gnanaguru; Charandeep Singh (Communications Biology)
Abstract Activation of anaplerosis takes away glutamine from the biosynthetic pathways to the energy-producing TCA cycle. Especially, induction of hyperoxia driven anaplerosis in neurovascular tissues such as the retina during early stages of development could deplete biosynthetic precursors from newly proliferating endothelial cells impeding physiological angiogenesis and leading to vasoobliteration. Using an oxygen-induced retinopathy (OIR) mouse model, we investigated the metabolic differences between OIR-resistant BALB/cByJ and OIR susceptible C57BL/6J strains at system levels to understand the molecular underpinnings that potentially contribute to hyperoxia-induced vascular abnormalities in the neural retina. Our systems level in vivo RNA-seq, proteomics, and lipidomic profiling and ex-vivo retinal explant studies show that the medium-chain fatty acids serves as an alternative source to feed the TCA cycle. Our findings strongly implicate that medium-chain fatty acids could suppress glutamine-fueled anaplerosis and ameliorate hyperoxia-induced vascular abnormalities in conditions such as retinopathy of prematurity.